2018
DOI: 10.1007/s40095-018-0287-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessments of binned and support vector regression-based blade pitch curve of a wind turbine for the purpose of condition monitoring

Abstract: The unexpected failure of wind turbine components leads to significant downtime and loss of revenue. To prevent this, supervisory control and data acquisition (SCADA) based condition monitoring is considered as a cost-effective approach. In several studies, the wind turbine power curve has been used as a critical indicator for power performance assessment. In contrast, the application of the blade pitch angle curve has hardly been explored for wind turbine condition monitoring purposes. The blade pitch angle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…For these reasons, in order to compare reliably the performance of the same model of wind turbine placed in different sites, it is more appropriate to compare operation curves that are not based on the nacelle wind speed measurements: in this study, the same curves as in [25] are selected, which are the generator speed-power curve and the blade pitchpower curve. In studies like [34][35][36], it was observed that operation variables as the rotor speed, generator speed, and blade pitch are important for a reliable multivariate analysis of the power of a wind turbine [37,38]. In this study, following [38], a step forward with respect to the literature is made because the selected curves involve couples of operation variables and do not involve the nacelle wind speed.…”
Section: Operation Curve Analysismentioning
confidence: 99%
“…For these reasons, in order to compare reliably the performance of the same model of wind turbine placed in different sites, it is more appropriate to compare operation curves that are not based on the nacelle wind speed measurements: in this study, the same curves as in [25] are selected, which are the generator speed-power curve and the blade pitchpower curve. In studies like [34][35][36], it was observed that operation variables as the rotor speed, generator speed, and blade pitch are important for a reliable multivariate analysis of the power of a wind turbine [37,38]. In this study, following [38], a step forward with respect to the literature is made because the selected curves involve couples of operation variables and do not involve the nacelle wind speed.…”
Section: Operation Curve Analysismentioning
confidence: 99%
“…For this reason, therefore, in the wind energy literature, the idea of employing the rotor as wind speed measurement probe has been recently gaining interest: this is the concept of rotor equivalent wind speed [23,24]. Thus, the performance monitoring task can translate into the monitoring of appropriate operation curves (alternative to the power curve), like the rotor speed-power curve [25] and the blade pitch-power curve [25,26].…”
mentioning
confidence: 99%
“…Support vector regression has been vastly employed in general for renewable power generation applications [30] and in particular for several kinds of problem in wind energy, such as, for example, operation curve analysis [31,32], wind farm layout optimization [33], and forecasting [34,35].…”
Section: Support Vector Regressionmentioning
confidence: 99%